Should the Samuelson Rule Be Modified to Account for the Marginal Cost of Public Funds? - Dan Usher (Queen's University, Department of Economics, 2006)
Disputes over the marginal cost of public funds may be about its magnitude in any given time and place or about its role in cost-benefit analysis. This paper is about the latter. The Samuelson rule was devised for an omnipotent, omniscient and benevolent government. This paper is about how the Samuelson rule should be modified to take account of the impact upon total deadweight loss in the tax system from the required an increase in the tax rate to finance public projects as well as from the appearance of the projects themselves. A very simple device is employed to analyze these questions.
Keywords: H41; H43; 330; Samuelson rule; Marginal cost of public funds; Shadow price of public expenditure